A Review of Antiplatelet Activity of Traditional Medicinal Herbs on Integrative Medicine Studies. (3rd January 2019) - Kim, Kyungho; Park, Kwang-Il
Abstract : Thrombotic events mainly occurred by platelet activation and aggregation. The vascular occlusion causes serious disease states such as unstable angina, ischemic stroke, and heart attack. Due to the pervading of thrombotic diseases, new antiplatelet drugs are necessary for preventing and treating arterial thrombosis without adverse side effects. Traditional medicinal herbs have been used for the treatment of human ailments for a long time. The clinically useful and safe products from traditional medicinal herbs were identified and developed in numerous pharmacological approaches. A complementary system of traditional medicinal herbs is a good candidate for pharmacotherapy. However, it still has a limitation in its function and efficacy. Thus, it is necessary to study the mode of action of traditional medicinal herbs as alternative therapeutic agents. In this review, we focused on our current understanding of the regulatory mechanisms of traditional medicinal herbs in antiplatelet activity and antithrombotic effect of traditional medicinal herbs on platelet function.